Effectiveness of Reversible Contraception in Dog Population Management - Baquero, Oswaldo Santos; Brandão, Ana Pérola Drulla; Amaku, Marcos; Ferreira, Fernando (Acta Scientiae Veterinariae, 2016)
Background: Dog fertility depends on human-influenced factors such as sterilization. Uncontrolled fertility can result in unwanted births and overpopulation, which causes problems of public health and animal welfare. Surgical sterilization has been the traditional means of reproduction control but its cost and time can be prohibitive for mass sterilization programs. Non-surgical sterilization alternatives exist, but most of them are reversible and their effectiveness as a population management tool is unknown. To better understand the consequences of reversible contraception, the fertility dynamics was modeled in a hypothetical dog population in a steady-state condition. Materials, Methods & Results: The effect of reversible contraception was simulated using a coupled system of ordinary differential equations. A hypothetical steady-state population of 1000 animals was considered. It was formed by two compartments, one of fertile dogs and the other of infertile dogs. Natality compensated for a fraction of mortality, and the immigration rate compensated for the remaining fraction. The group of immigrant dogs was composed of fertile and infgertile dogs. The dog flow between compartments was given by both the contraception and fertility recovery rate. It was assumed that fertility reversibility in animals of the immigrant group was equal to that of animals already present in the population. Global sensitivities were calculated to assess the uncertainties of fertility dynamics associated with estimation of parameters. In addition, the local sensitivities were calculated to assess the influence of each parameter on fertility dynamics. The treatment effectiveness were expressed in terms of the total number of dogs treated for 20 years by taking a given irreversible contraception rate divided by the total number of dogs treated during the same period, and using the corresponding reversible contraception rate. The global sensitivity analysis consistently indicated a reduction in the number of fertile dogs. The local sensitivity analysis indicated that contraception rate was the most influential parameter, followed by the fertility recovery rate. The fraction of mortality compensated by natality was more influential than the fraction of infertile immigrants. Simulated scenarios indicated that the higher the contraception rate, the greater the difference between the effects of different fertility recovery rates. Variations in the proportion of infertile immigrants minimally changed the number of fertile dogs and the accumulated number of treated dogs. The increase in the fertility recovery rate caused effectiveness to decrease, especially when contraception rates were higher. Discussion: In certain scenarios, reversible contraception can be a viable option for reproduction control. Evaluation of effectiveness of the reversible contraception showed both the importance of duration of the contraceptive effect and the interaction between the contraception and fertility recovery rates. Although the contraception rate is the main determinant of population fertility dynamics, the fertility recovery rate modulates the effect of contraception and determines its viability. Reversible contraception is a viable alternative when loss in effectiveness is compensated by a reduction in costs and ease of application of contraceptive treatments. The lower the contraception rate, the higher the similarity between the effects of reversible and irreversible contraception.